2022
DOI: 10.1111/ajo.13509
|View full text |Cite
|
Sign up to set email alerts
|

Single‐centre survey of women reflecting on recent experiences and preferences of oral intake during labour

Abstract: Background: Consensus-based recommendations guiding oral intake during labour are lacking. Aims:We surveyed women at a tertiary women's hospital about preferences for and experiences of oral intake during labour, gastrointestinal symptoms during labour and recalled advice about oral intake. Materials and methods:Women who experienced labour completed a postpartum survey with responses as free text, yes-no questions and five-point Likert scales. We identified demographic data and risk factors for surgical or an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“… 28 These issues can be resolved through isotonic IVT types; however, it warrants the question as to whether women can be adequately hydrated via the oral route during labor? Current guidance is that women should not be routinely fasted during labor and birth 6 and studies highlight that women prefer having control over what they ingest during labor and birth, 12 yet this occurs within a context of conflicting advice and information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 These issues can be resolved through isotonic IVT types; however, it warrants the question as to whether women can be adequately hydrated via the oral route during labor? Current guidance is that women should not be routinely fasted during labor and birth 6 and studies highlight that women prefer having control over what they ingest during labor and birth, 12 yet this occurs within a context of conflicting advice and information.…”
Section: Discussionmentioning
confidence: 99%
“… 11 However, cesarean section was not reduced in women with unrestricted oral intake in their review. Oral intake during labor is preferred by women 12 during labor and there is no evidence of harm when they self‐regulate oral intake for nourishment, comfort, and hydration. 8 Consistent with this, international guidelines recommend oral intake in labor 6 and this is the usual practice in many maternity units internationally.…”
Section: Introductionmentioning
confidence: 99%
“…10 More recently, advances in regional anesthesia and concurrent reduction in rates of general anesthesia, means routine fasting, especially for women at low risk of complications in spontaneous labor, has become less common. 11 Subsequently, international intrapartum guidelines now encourage oral fluid intake during labor. 12,13 International intrapartum care guidelines, for a positive birth experience 12 recommend that maternal hydration should be managed by way of oral fluid and food intake during labor.…”
Section: Introductionmentioning
confidence: 99%
“…birth, clinical variation, fasting in labor, hydration, hyponatremia, intrapartum care, intravenous therapy, labor, labor and birth management or care systematic review (seven trials) found that IVT therapy did not reduce the duration of labor. 24 Notably, the control groups fasted intrapartum-a practice now discouraged by international intrapartum guidelines 12 or maternal preference 11 and therefore limiting applicability to current practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation